ERLEKS: en estnisk-svensk lexikalisk databas - Cousins, Signe (Nordiske Studier i Leksikografi, 1997)
There is an Estonian-Swedish parallel corpus currently under construction at the Department of Scandinavian Studies, University of Tartu. It is being built according to the example of some already existing translation corpora. The corpus was first and foremost meant as a completion toa new and comprehensive Swedish-Estonian dictionary, but there have appeared other fields of application and research in connection with it: an authentic lexical source material for different glossaries and dictionaries, an active study aid for the students of Swedish, a source ofresearch material for the study of collocations and constructions as well as of differences in sentence construction and word order ofthe two languages.